Cross-sector analysis of the Hungarian sectors covered by the Effort Sharing Decision – Climate policy perspectives for the Hungarian agriculture within the 2021-2030 EU programming period - Fogarassy, Csaba; Horváth, Bálint; Kovács, Attila (Applied Studies in Agribusiness and Commerce, 2015)
Ever since 2012, the EU ETS (European Union’s Emission Trading Scheme), which is the EU’s climate policy was extended to include the ESD (Effort Sharing Decision) sectors’ (agriculture, transport, building) regulations. As its name implies, this mechanism is based off of shared interests and efforts, all in order to reach the climate goals. Therefore, analysing the agriculture sector from an environmental viewpoint requires the analysis of related sectors as well, since their performances will have an impact on determining the requirements to be met by the agriculture. Seeing that those primarily present in said sectors are not various firms, but people and public utility management institutions instead, the level of regulations draws from the economic state of the various countries in question (GDP per capita). Therefore, member states like ours did not receive difficult goals until 2020, due to our performance being lower than the average of the EU. However, during the program phase between 2021 and 2030, all nations are to lower their GHG (greenhouse gases) emission, and have to make developments to restrict GHG emission level growth within the ESD, which means we already have to estimate our future possibilities. During the analyses, we will see that analysing agriculture from an environmental viewpoint, without doing the same to their related sectors and their various related influences is impossible. The GHG emission goals determined by the EU have to be cleared by the agriculture sector, but the inputs from transport, waste management and building are required nonetheless.JEL classification: Q58